Library usage patterns in the electronic information environment. Electronic journals, Use studies, Libraries, Medical libraries - B. Franklin; T. Plum (Information Research: An International Electronic Journal)
This paper examines the methodology and results from Web-based surveys of more than 15,000 networked electronic services users in the United States between July 1998 and June 2003 at four academic health sciences libraries and two large main campus libraries serving a variety of disciplines. A statistically valid methodology for administering simultaneous Web-based and print-based surveys using the random moments sampling technique is discussed and implemented. Results from the Web-based surveys showed that at the four academic health sciences libraries, there were approximately four remote networked electronic services users for each in-house user. This ratio was even higher for faculty, staff, and research fellows at the academic health sciences libraries, where more than five remote users for each in-house user were recorded. At the two main libraries, there were approximately 1.3 remote users for each in-house user of electronic information. Sponsored research (grant funded research) accounted for approximately 32% of the networked electronic services activity at the health sciences libraries and 16% at the main campus libraries. Sponsored researchers at the health sciences libraries appeared to use networked electronic services most intensively from on-campus, but not from in the library. The purpose of use for networked electronic resources by patrons within the library is different from the purpose of use of those resources by patrons using the resources remotely. The implications of these results on how librarians reach decisions about networked electronic resources and services are discussed.